The Utilization of Online Video for Promotional and User Education Activities in Library of Ma Chung University - Tri Mega Asri; Akhmad Rizki Pranata (Program Pendidikan Vokasi Universitas Brawijaya, 2015)
The Promotional and User Education activities are methods which have been implemented in library context. These methods can be applied by using a video. The video that will be shared on social media is dedicated to all users of Library of Ma Chung University.The media that have been selected to share this video are Youtube and Gmail which is connected to all of social media to spread the video to all users of Library of Ma Chung University. This video explains how to use sphisticated facility in this digital era which is supported with the incredilble information development. The Utilization of this online video can increase the number of guests in library and make the facilites usage more effective so the library can operate well based on its function.